China's BRI and the evolving rules in international dispute resolution - Zhong, Mariana (Henry Stewart Talks, 2019)
Belt and road initiative (BRI) historical background, Modern BRI, Scale of BRI, Investors, International commercial and investment arbitration, China’s role in international investment arbitration, Investment cases against China, Suggestions for investors